2022
DOI: 10.1039/d1qi01539g
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the formation of oxygen vacancies in ceria multishelled hollow microspheres by doping iron for enhanced ambient ammonia electrosynthesis

Abstract: Electrochemical nitrogen reduction reaction (NRR) is an environmentally friendly and sustainable approach for NH3 synthesis at mild pressure and temperature, but implementation depends on efficient electrocatalysts. Herein, iron-doped ceria multishelled...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…For example, Sun and co-workers introduced Fe dopants into the ceria multishelled hollow microspheres, which could increase the OVs concentration, exposed more catalytic active sites, and optimized the nitrogen adsorption energy, thereby enhancing the catalytic NRR performance. 37 The coupling of XPS and Raman results indicated that Fe–CeO 2 possessed abundant OVs. It was identified that unsaturated Ce 3+ sites with high electron density next to oxygen vacancies can effectively adsorb free N 2 molecules through rapid electron transfer, thus enhancing the NRR performance.…”
Section: Defect Engineeringmentioning
confidence: 98%
“…For example, Sun and co-workers introduced Fe dopants into the ceria multishelled hollow microspheres, which could increase the OVs concentration, exposed more catalytic active sites, and optimized the nitrogen adsorption energy, thereby enhancing the catalytic NRR performance. 37 The coupling of XPS and Raman results indicated that Fe–CeO 2 possessed abundant OVs. It was identified that unsaturated Ce 3+ sites with high electron density next to oxygen vacancies can effectively adsorb free N 2 molecules through rapid electron transfer, thus enhancing the NRR performance.…”
Section: Defect Engineeringmentioning
confidence: 98%
“…Ammonia is vital to human production and plays an important role in fertilizer production and clean energy applications. 100 Currently, ammonia is synthesized industrially mainly by the Haber-Bosch process, but the reaction conditions are harsh, requiring high temperatures (>673 K) and pressures (>700 bar), and are very energy intensive (about 1-2% of all human energy consumption). It also contributes to the emission of greenhouse gases such as CO 2 , which leads to climate change such as acid rain and environmental damage.…”
Section: Mof-based Electrocatalysts For the Nitrogen Reduction Reactionmentioning
confidence: 99%
“…The structural design of materials is the main factor affecting their properties. [16][17][18][19][20] Two-dimensional (2D) van der Waals heterostructures with the integrated advantages of two 2D nanomaterials are an emerging electrode material system in the field of energy storage. [21][22][23][24][25][26] It is worth noting that bismuth oxychloride (BiOCl) features a layered structure with [Cl-Bi-O-Bi-Cl] slices stacking through the weak van der Waals interaction among adjacent Cl layers.…”
Section: Introductionmentioning
confidence: 99%